Genome‐wide identification and analysis of microRNA responding to long‐term waterlogging in crown roots of maize seedlings. Issue 2 (27th June 2012) - Zhai, Lihong; Liu, Zhijie; Zou, Xiling; Jiang, Yuanyuan; Qiu, Fazhan; Zheng, Yonglian; Zhang, Zuxin
<x xml:space="preserve">Abstract</x> MicroRNAs (miRNAs) are critical post‐transcriptional modulators of gene expression involving in plant responses to abiotic stress. However, the regulation of miRNA in the morphological response to waterlogging is poorly understood in maize. In this study, we detected miRNAs and their targets that expressed in waterlogged crown roots of maize seedlings in two inbred lines (Hz32 and Mo17) by RNA sequencing. A total of 61 mature miRNAs were found including 36 known maize (zma) miRNAs and 25 potential novel miRNA candidates. Comparison of miRNA expression in both waterlogged and control crown roots revealed 32 waterlogging‐responsive miRNAs, most were consistently downregulated under waterlogging in the two inbred lines. We identified the miRNA targets through degradome sequencing. Many known miRNA targets involving in transcription regulation and reactive oxygen species elimination were found in the degradome libraries, and 17 targets of 10 newly detected miRNAs were identified as well. Moreover, the miRNA‐mediated pathways that respond to waterlogging and regulate the induction of crown roots were discussed. This study is a comprehensive survey of responsive miRNAs in waterlogged maize crown roots. The results will help to understand the miRNA expression in response to waterlogging and miRNA‐mediated regulation of morphological adaptation to waterlogging in maize.